Inhibition of HIV-1 infection of peripheral blood mononuclear cells by a monoclonal antibody that binds to phosphoinositides and induces secretion of β-chemokines - Matyas, Gary R. (Biochem Biophys Res Commun, 2010)
A murine IgG mAb, WR321, selected for the ability to bind to phosphatidylinositol-4-phosphate and phosphatidylinositol-4,5-bisphosphate, but an inability to bind to any of 17 other lipids, including phosphatidylinositol, was examined as a probe for studying interactions of HIV-1 with primary human peripheral blood mononuclear cells. The WR321 mAb broadly neutralized CCR5-tropic strains of HIV-1 to prevent infection of the cells. The mAb also exhibited direct interaction with cells in the culture, resulting in secretion of chemokines that interfered with the interaction of HIV-1 virions with CCR5, the coreceptor for HIV-1 on the susceptible cells, leading to inhibition of infection by HIV-1. Phosphoinositides that are recognized by WR321 do not exist on the external surface of cells, but are concentrated on the inner surface (cytoplasmic leaflet) of the plasma membrane. Murine anti-phosphoinositide mAbs similar to WR321 have previously been directly microinjected into a variety of cultured cells, resulting in important changes in the functions of the cells. The present results suggest that binding of a mAb to phosphoinositides, resulting in secretion of β-chemokines into the culture medium and neutralization of infection by CCR5-tropic HIV-1 of nearby susceptible cells, occurred by uptake and binding of the mAb at an intracellular location in the cultured cells that then led to secretion of HIV-1-inhibitory β-chemokines.